1972
DOI: 10.1177/007542427200600104
|View full text |Cite
|
Sign up to set email alerts
|

Directions of Change in Southern California English

Abstract: has attributed to the miners of California a peculiar, strongly-marked, and affected dialect, but he has drawn on his imagination for the greater part of it. A mixed population like that in the mines, representing every state in the Union, and every county of Great Britain, could not have a dialect; and nowhere is the English language better understood, or spoken with more force, elegance, and purity, by the poorer classes of people, than in this State. 1 If you want to hear the general American of the future,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In an early study of California language variation, Metcalf (1972) found lexical and phonological leveling in Riverside relative to the Linguistic Atlas of the Pacific Coast (LAPC). Lexical forms such as couch or bag (vs. sofa or sack) that were slightly dominant when the LAPC was compiled had become more dominant in Metcalf's surveys.…”
Section: English Language Variation In Californiamentioning
confidence: 99%
“…In an early study of California language variation, Metcalf (1972) found lexical and phonological leveling in Riverside relative to the Linguistic Atlas of the Pacific Coast (LAPC). Lexical forms such as couch or bag (vs. sofa or sack) that were slightly dominant when the LAPC was compiled had become more dominant in Metcalf's surveys.…”
Section: English Language Variation In Californiamentioning
confidence: 99%
“…It is found throughout the South (Brown 1991;Montgomery & Elbe 2004;Tillery & Bailey 2004), though it is also present at scattered points across the US (Metcalf 1972;Bigham 2005;ANAE). In the South, it has been found to be receding recently in large urban centres such as Houston (Koops et al 2008), Dallas and Atlanta (Tillery & Bailey 2004), likely due to a large influx of non-Southerners in the last few decades (Thomas 1997(Thomas , 2004.…”
Section: Introductionmentioning
confidence: 99%
“…The pin鈥損en merger is a conditioned merger of /瑟/ and /蓻/ before front nasals, as in pin鈥損en, him鈥揾em, sinned鈥搒end , etc. It is found throughout the South (Brown 1991; Montgomery & Elbe 2004; Tillery & Bailey 2004), though it is also present at scattered points across the US (Metcalf 1972; Bigham 2005; ANAE). In the South, it has been found to be receding recently in large urban centres such as Houston (Koops et al .…”
Section: Introductionmentioning
confidence: 99%
“…The fronting of /u/ has been documented in a host of dialects and areas of the English-speaking world. The F2 of /u/ is rising, in, among other varieties, British English (Gimson, 1970), in California English (Metcalf, 1972;Hinton et al, 1987), in M膩ori English and New Zealand English (Maclagan et al, 2009), and in the South of the US (Bailey, 1997). In this section I present results of an acoustic analysis comparing data from the Nationwide Speech Corpus (NSC: Clopper & Pisoni, 2006) and Lang & Davidson (2016), which reveals acoustic changes in the English vowel system in the Northeast US.…”
Section: U-frontingmentioning
confidence: 93%